Igneous Rock Associations 19. Greenstone Belts and Granite−Greenstone Terranes: Constraints on the Nature of the Archean World - Thurston, P. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2015)
Greenstone belts are long, curvilinear accumulations of mainly volcanic rocks within Archean granite−greenstone terranes, and are subdivided into two geochemical types: komatiite− tholeiite sequences and bimodal sequences. In rare instances where basement is preserved, the basement is unconformably overlain by platform to rift sequences consisting of quartzite, carbonate, komatiite and/or tholeiite. The komatiite−tholeiite sequences consist of km-scale thicknesses of tholeiites, minor intercalated komatiites, and smaller volumes of felsic volcanic rocks. The bimodal sequences consist of basal tholeiitic flows succeeded upward by lesser volumes of felsic volcanic rocks. The two geochemical types are unconformably overlain by successor basin sequences containing alluvial–fluvial clastic metasedimentary rocks and associated calc-alkaline to alkaline volcanic rocks. Stratigraphically-controlled geochemical sampling in the bimodal sequences has shown the presence of Fe-enrichment cycles in the tholeiites, as well as monotonous thicknesses of tholeiitic flows having nearly constant MgO, which is explained by fractionation and replenishment of the magma chamber with fresh mantle-derived material. Geochemical studies reveal the presence of boninites associated with the komatiites, in part a result of alteration or contamination of the komatiites. Within the bimodal sequences there are rare occurrences of adakites, Nb-enriched basalts and magnesian andesites. The greenstone belts are engulfed by granitoid batholiths ranging from soda-rich tonalite−trondhjemite−granodiorite to later, more potassic granitoid rocks. Archean greenstone belts exhibit a unique structural style not found in younger orogens, consisting of alternating granitoid-cored domes and volcanicdominated keels. The synclinal keels are cut by major transcurrent shear zones. Metamorphic patterns indicate that low-pressure metamorphism of the greenstones is centred on the granitoid batholiths, suggesting a central role for the granitoid rocks in metamorphosing the greenstones. Metamorphic patterns also show that the proportion of greenstones in granite−greenstone terranes diminishes with deeper levels of exposure. Evidence is presented on both sides of the intense controversy as to whether greenstone belts are the product of modern plate tectonic processes complete with subduction, or else the product of other, lateral tectonic processes driven by the ‘mantle wind.’ Given that numerous indicators of plate tectonic processes – structural style, rock types, and geochemical features − are unique to the Archean, it is concluded that the evidence is marginally in favour of non-actualistic tectonic processes in Archean granite−greenstone terranes.